+0  
 
0
26
2
avatar

Let a and b be the roots of x^2 - 5x + 143 = 0.  Find (a - 1)(b - 1).

 May 12, 2020
 #1
avatar+20792 
+1

x2 - 5x + 143  =  0

 

Using the quadratic formula:     a  =  [ 5 + i·sqrt(547) ] / 2     and     b  =  [ 5 - i·sqrt(547) ] / 2 

 

a - 1  =  [ 5 + i·sqrt(547) ] / 2  - 1  =  5/2  +  i·sqrt(547)/2 - 1  =  3/2 +  i·sqrt(547)/2  

b - 1  =  [ 5 - i·sqrt(547) ] / 2  - 1  =  5/2  -  i·sqrt(547)/2 - 1  =  3/2 -  i·sqrt(547)/2  

 

(a - 1)(b - 1)  =  [ 3/2 + i·sqrt(547)/2 ] · [ 3/2 - i·sqrt(547)/2 ]  =  9/4 - i2·547/4  =  139  

 May 12, 2020
 #2
avatar+111360 
+1

THX, geno......here's another way

 

The sum of  the roots  =  -(-5)/1  =  5  =  a + b

 

The product of the  roots =  143/1 =  143  = ab

 

So

 

(a - 1) (b - 1)   =

 

ab  - a - b +  1  =

 

ab - (a + b)  + 1  =

 

143  - (5)  +  1  =

 

139

 

 

cool cool cool

 May 12, 2020

15 Online Users

avatar
avatar
avatar